Biochemical markers of alcohol use and their clinical aplications - Mırsal, Hasan; Kalyoncu, Ö. Ayhan; Pektaş, Özkan (Journal of Dependence, 2002)
Biochemical markers to detect excessive alcohol use are important for screening, treatment, and preventin of alcohol dependency and other alcohol-related medical diseases. These markers may also promote public health areas.In some countries, these markers are tested for identifying of heavy drinkers in occupational fields. To achieve these goals, biochemical markers must be characterized by several important features. These features include reliability, validity, stability, cost, practibility, acceptability, transportability. Unfortunately, to date, no single marker satisfies all these features. Traditional markers are low to moderate sensitivity, frequently false positives, poorly specified relationships with the amount of alcohol use. The most commonly used tests are gamma glutamyl transferase, alanine aminotransferase, aspartate aminotransferase, mean corpusculer volume and the newest marker, carbohydrate- deficient transferrin. Nowadays several new tests are under development. These include Early Detection of Alcohol Consumption Test, Hemoglobin Associated Acetaldehyde Assay and measures of fatty acid ethyl esters, and alcohol vapor at the skin surface. In his article, the literature of biochemical markers of alcohol use have been reviewed.